Sebastián Salazar Bondy: alabanza y crítica del tradicionalismo limeño - Granda, Mario (2018)
He studies the previous intellectual production of Salazar Bondy, his articles published between the years 1950-1964 where he was gestating the topics that later became one of the hardest criticisms of the Limeñista traditionalism of the twentieth century with the essay Lima the horrible (1964), where he performs a scrupulous analysis of the customs, literature, painting and other artistic and social Lima that he considers part of this traditionalism and, consequently, they project a conservative and pasadista image about the city and society. The study allows us to know what were the ideas and budgets on which he left to write his well-known essay